La ciudad amable y hostil: Bucarest al borde de la guerra - Oancea, Ruxandra (Revista de Filología Románica, 2011)
Considering aspects as diverse as Romania’s joining II World War, the life of the elites or the decay around the poorest inhabitants of the capital city, Olivia Manning takes on an impressive, comprehensive fresco of the city of Bucharest in the harsh times following the outbreak of the war. In the confrontation between the Western and the Balkan cultures, under the sharp eye of a non conformist young English woman, Bucharest remains a strange, unknown, alien place.